Academic authorship: who, why and in what order? - Hundley, V; Teijlingen, Evan; Simkhada, P (Health Renaissance, 2013)
Health Renaissance, January-April 2013; Vol. 11 No.1; 99-101 DOI: http://dx.doi.org/10.3126/hren.v11i2.8214